Human platelet lysate: a potential therapeutic for intracerebral hemorrhage - Qiu, Dachang; Wang, Lin; Wang, Lanlan; Dong, Yongfei (Frontiers in Neuroscience, 2025)
Intracerebral hemorrhage (ICH) is a major public health challenge worldwide, and is associated with elevated rates of mortality, disability, and morbidity, especially in low- and middle-income nations. However, our knowledge of the detailed molecular processes involved in ICH remains insufficient, particularly those involved in the secondary injury stage, resulting in a lack of effective treatments for ICH. Human platelet lysates (HPL) are abundant in bioactive factors, and numerous studies have demonstrated their beneficial effects on neurological diseases, including their anti-neuroinflammatory ability, anti-oxidant effects, maintenance of blood–brain barrier integrity, and promotion of neurogenesis. In this review, we thoroughly explore the potential of HPL for treating ICH from three critical perspectives: the rationale for selecting HPL as a treatment for ICH, the mechanisms through which HPL contributes to ICH management, and the additional measures necessary for HPL as a treatment for ICH. We elucidate the role of platelets in ICH pathophysiology and highlight the limitations of the current treatment options and advancements in preclinical research on the application of HPL in neurological disorders. Furthermore, historical developments and preparation methods of HPL in the field of biomedicine are discussed. Additionally, we summarize the bioactive molecules present in HPL and their potential therapeutic effects in ICH. Finally, we outline the issues that must be addressed regarding utilizing HPL as a treatment modality for ICH.